Using an Artificial Intelligence Based Program to Enhance Primary Stage Pupils' EFL Listening Skills - Ghoneim, Nahed Mohammed Mahmoud; Elghotmy, Heba Elsayed Abdelsalam (جامعة سوهاج - كلية التربية, 2021)
هدفت الدراسة الحالية إلى التحقق من فعالية برنامج قائم على الذكاء الاصطناعي (AI) في تطوير مهارات الاستماع في اللغة الإنجليزية لدى تلاميذ الصف السادس الابتدائي. شمل المشاركون في الدراسة (80) تلميذا مقسمين إلى مجموعتين: المجموعة التجريبية (ن= 40) التي تم تدريسها باستخدام برنامج قائم على الذكاء الاصطناعي بينما تلقت المجموعة الضابطة (ن = 40) التدريس باستخدام الطريقة العادية. وقد تضمنت أدوات الدراسة: قائمة لمهارات الاستماع للغة الإنجليزية كلغة أجنبية لتحديد أهم مهارات الاستماع لدى تلاميذ الصف السادس الابتدائي، واختبار لقياس مهارات الاستماع قبل وبعد تطبيق البرنامج. وقد أظهرت نتائج الدراسة فاعلية البرنامج القائم على الذكاء الاصطناعي في تنمية مهارات الاستماع في اللغة الإنجليزية لدى تلاميذ المجموعة التجريبية.
Appreciating the opportunities and challenges that artificial intelligence (AI) creates, made it important to verify what AI is today and what the future may bring when it is widely used in education. The current study aimed at investigating the effectiveness of an artificial intelligence (AI) based program in Enhancing EFL listening skills among sixth year primary stage pupils. The participants of the study included (80) pupils divided into two groups: the experimental group (N=40) that was taught using the Artificial Intelligence based program and the control group (N=40) that received regular instruction. The instruments of the study included: an EFL listening skills checklist to determine the most important listening skills to be developed by sixth year primary stage pupils, a pre-post listening skills test to measure pupils' listening skills before and after implementing the program, and a rubric for correction. Data was analyzed statistically to verify the study hypotheses. Findings of the study revealed that the experimental group pupils' EFL listening skills were enhanced as a result of using the Artificial Intelligence based program.
Keywords: التعليم الابتدائي -- تدريس اللغة الإنجليزية -- مهارات الاستماع -- الذكاء الاصطناعي